Tradução, adaptação e validação da escala self-efficacy and their child's level of asthma control : versão brasileira - Gomes, Ana Lúcia Araújo (2015)
Efforts to improve the self-efficacy of parental care in the care of childhood asthma can result in control of the disease. The objective was to translate, adapt and validate the Self-Efficacy and Their Child's Level of Asthma Control scale into Portuguese and verify the reliability and validity of the instrument to detect the self-efficacy of parental care in the control of childhood asthma. To perform the evaluation stage of the psychometric properties was made, first the translation and cultural adaptation of Self-Efficacy and Their Child's Level of Asthma Control of asthma control in the Brazilian version from the guidelines Beaton et al. (2007). After the adaptation process, we obtained a range of 17 items with five response options (from strongly disagree to strongly agree). By also dealing with a methodological type of research with a quantitative approach, the scale was submitted to validity and reliability. Seven judges performed the content validity guided Pasqualy (2010), reaching an acceptable CVCT, keeping the total of items and the original scale score (17-85 points). The clarity of language dimensions, relevance practical and theoretical relevance, showed respectively a total CVCT of 0.88, 0.90 and 0.89. Data collection through a home visit was realized from August 2014 to January 2015. A sample of 216 parents who care of children with asthma, regularly monitored in PROAICA one of the three Primary Care Units Fortaleza SER I, said in addition to the scale, a sociodemographic questionnaire and issues related to children's health. Exploratory factor analysis was adequate to evaluate the Brazilian version (Kaiser- Meyer-Olkim- 0.879 and sphericity Bartlett p<0.001) confirmed the existence of two factors (expectation of efficacy and expected results) and suggested withdrawal item 07 of the Brazilian version of the scale. The testing of hypotheses has been proven, as it was found that “parents who care” with less than nine years of schooling, obtained lower scores in self-efficacy in the control of childhood asthma and “parents who care” with higher scores of self-efficacy achieved better asthma control parameters Children. Thus, the validity of the construct by contrasted groups found a statistically significant association between self-efficacy levels and the following variables: age (p=0.019), education (p=0.001); occupation of parents (p=0.015 unscheduled physician visits (p=0.001), visits to emergencies (p=0.000), hospitalization in the last 12 months (p=0.005), limitation of physical activity (p=0.003), absenteeism school (p=0.000), disturbed sleep (p=0.000) and to differentiate the control medication crisis medication (p=0.004), among others. The Cronbach's alpha was 0.87, with 17 items demonstrated high Internal consistency of the instrument, attested by the ICC (p=0.001, CI=95%). with an average of 0.871 Considering the withdrawal of item 07, the Cronbach's alpha with 16 items resulted in a value of 0.92 ., maintaining the scale as a reliable tool Test-retest stability was calculated using the Spearman-Brown coefficient (0.80) and Pearson's correlation coefficient (r=0.65; p=0.001), showing that the correlation the results of the two applications is strongly positive. It was concluded therefore that it obtained a reliable instrument, valid and able to assess the reliability and the expected results of the “parents who care” in the control of childhood asthma instrument.